The role of annexin A1 in Candida albicans and Candida auris infections in murine neutrophils. (January 2021) - Sanches, José Marcos; Rossato, Luana; Lice, Izabella; Alves de Piloto Fernandes, Anna Maria; Bueno Duarte, Gustavo Henrique; Rosini Silva, Alex Aparecido; de Melo Porcari, Andreia; de Oliveira Carvalho, Patrícia; Gil, Cristiane Damas
Abstract: Annexin A1 (AnxA1) is an anti-inflammatory protein expressed in various cell types, especially macrophages and neutrophils. Because neutrophils play important roles in infections and inflammatory processes and the relationship between AnxA1 and Candida spp. infections is not well-understood, our study examined whether AnxA1 can serve as a target protein for the regulation of the immune response during fungal infections. C57BL/6 wild-type (WT) and AnxA1 knockout (AnxA1 −/− ) peritoneal neutrophils were coinfected with Candida albicans or Candida auris for 4 h. AnxA1 −/− neutrophils exhibited a marked increase in cyclooxygenase 2 (COX-2), phosphorylated extracellular signal-related kinase (ERK), p-38, and c-Jun N-terminal kinase (JNK) levels after coinfection with both Candida spp. A lipidomics approach showed that AnxA1 deficiency produced marked differences in the supernatant lipid profiles of both control neutrophils and neutrophils coinfected with Candida spp. compared with WT cells, especially the levels of glycerophospholipids and glycerolipids. Our results showed that endogenous AnxA1 regulates the neutrophil response under fungal infection conditions, altering lipid membrane organization and metabolism. Highlights: The lack of Annexin A1 in neutrophils promotes high levels of MAPKs and COX-2 expressions. AnxA1 −/− per se evidenced a different lipid profile in murine neutrophils. Annexin A1 regulates the neutrophil response in Candida albicans and Candida auris infections.